2015
DOI: 10.14737/journal.jahp/2015/3.3.64.72
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Selenium-methionine Nanocomposite as a Novel Dietary Supplement for Laying Hens

Abstract: Recently, nanotechnology introduced new modality in the field of broiler nutrition through the benefits of the unique properties at the nanoscale such as increasing surface area, high absorption and lower toxicity. However, there is insufficient available data about the utilization of nano compounds in laying hens. Wang (2009) found that nano-Selenium increased muscle selenium concentration in broilers than sodium selenite. Therefore, the purpose of this study was to assess the nutritional effects of Seleni- R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Nutrient digestibility may have been increased by pelleting in contrast to mash rations (Zelenka, 2003). Some most recent studies have used advanced techniques like nanotechnology that were also based on the same hypothesis as we have adopted in our study (Salah-Eldin et al, 2015). Greenwood et al (2005) demonstrated a high rate of growth and increased digestible lysine requirements for optimal WG and feed efficiency in pellet-fed broilers compared with mash-fed broilers from 16 to 30 d of age.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 94%
“…Nutrient digestibility may have been increased by pelleting in contrast to mash rations (Zelenka, 2003). Some most recent studies have used advanced techniques like nanotechnology that were also based on the same hypothesis as we have adopted in our study (Salah-Eldin et al, 2015). Greenwood et al (2005) demonstrated a high rate of growth and increased digestible lysine requirements for optimal WG and feed efficiency in pellet-fed broilers compared with mash-fed broilers from 16 to 30 d of age.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 94%
“…The method followed was modified using S. Malhotra et al, T.A.S. Eldin and U. Luesakul et al methods 7,10,11 . Biomaterial coating of Se NPs was conducted in‐situ; the first layer of coating was methionine (Met) used in a 1:5 ratio to the precursor volume.…”
Section: Methodsmentioning
confidence: 99%
“…The free radical scavenging ability of Se-Met-Fa NPs was studied by DPPH assay using the methods of S. Menon et al 6,15 with modifications. Different concentrations of Se-Met-Fa NPs were prepared (10,20,30,40,50, and 100 μg/ml). Ten milliliters of 0.1 mM DPPH solution was prepared in methanol, and 1 ml was added to each Se-Met-Fa NP s concentration.…”
Section: Antioxidant Assaymentioning
confidence: 99%
“…Salah et al [32] reported that egg yolk stored at room temperature for 15 days from hens receiving nano-selenium has higher activity of glutathione peroxidase and lower malondialdehyde content. The addition of nano selenium also improved the fatty acid profile in eggs by reducing the ratio of saturated to unsaturated fatty acids and also it significantly decreased the level of total lipids and total cholesterol, as well as increased the level of its high-density lipoprotein fraction in egg yolk and plasma of laying hens.…”
Section: Eggmentioning
confidence: 99%